Electrical properties of inhomogeneous tungsten carbide Schottky barrier on 4H-SiC. (9th November 2020) - Vivona, M; Greco, G; Bellocchi, G; Zumbo, L; Di Franco, S; Saggio, M; Rascunà, S; Roccaforte, F
Abstract: In this paper, the electrical behavior of tungsten carbide (WC) Schottky barrier on 4H-SiC was investigated. First, a statistical current-voltage (I–V) analysis in forward bias, performed on a set of equivalent diodes, showed a symmetric Gaussian-like distribution of the barrier heights after annealing at 700 °C, where a low Schottky barrier height (ΦB = 1.05 eV) and an ideality factor n = 1.06 were measured. The low value of the barrier height makes such a WC contact an interesting candidate to reduce the conduction losses in 4H-SiC Schottky diodes. A deeper characterization has been carried out, by monitoring the temperature dependence of the I–V characteristics and the behavior of the relevant parameters ΦB and n. The increase of the barrier height and decrease of the ideality factor with increasing temperature indicated a lateral inhomogeneity of the WC/4H-SiC Schottky contact, which was described by invoking Tung's model. Interestingly, the temperature dependence of the leakage current under reverse bias could be described by considering in the thermionic field emission model the temperature dependent barrier height related to the inhomogeneity. These results can be useful to predict the behavior of WC/4H-SiC Schottky diodes under operative conditions.